Respuesta :
Answer:
-6x + 17
Step-by-step explanation:
-(6x - 17)
= -6x + 17
=》Negative × negative = positive
=》 Positive × negative = negative
Hope it helps ⚜
Hi!
I can help you with joy!
- The Distributive Property states that
- a(b+c)=ab+ac
- Now, let's use this property to solve our problem:
- [tex]\sf{-(6x-17)[/tex]
- Think of the minus sign as being -1, and distribute:
- [tex]\sf{-6x+17}[/tex]
Answer:
-6x+17
Hope it helps.
Do ask if you have any queries regarding my answer.
[tex]\rm{PeacefulNature[/tex]